Financial Liberalization and Financial Fragility - Detragiache, Enrica; Demirguc-Kunt, Asli. (Washington, D.C. : International Monetary Fund, 1998)
A study of 53 countries during 1980-95 finds that financial liberalization increases the probability of a banking crisis, but less so where the institutional environment is strong. In particular, respect for the rule of law, a low level of corruption, and good contract enforcement are relevant institutional characteristics. The data also show that, after liberalization, financially repressed countries tend to have improved financial development even if they experience a banking crisis. This is not true for financially restrained countries. This paper's results support a cautious approach to financial liberalization where institutions are weak, even if macroeconomic stabilization has been achieved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet